The Model of Knowledge Management Components Relationships using Structural Equation Modeling - Abolfazl Salehi; Hossein Karimian; Gholamreza Sharifirad (Iranian Evolutionary Educational Psychology Journal, 2023)
The aim of the current research was to test the structural model of the relationships of knowledge management components in universities (Qom province universities) using structural equation modeling. The present study is an applied and correlation research. Participants were 247 faculty members of universities in Qom province selected via random sampling. The results of the model test showed that the effect of knowledge-oriented organizational culture, strategic planning of knowledge management, infrastructure of information and communication technology and knowledge manpower on knowledge management processes is positive and significant. The effect of knowledge management processes on knowledge-based human resource management, knowledge identification and goal setting, and knowledge team building is positive and significant. The effect of weakness in knowledge management rules and lack of motivation of employees and professors on knowledge-based human resource management, knowledge identification and goal setting, and knowledge team building is negative and significant. The effect of organizational structure and individual characteristics of employees and professors on knowledge-based human resource management, knowledge identification and goal setting, and knowledge team building is positive and significant. Finally, the impact of knowledge-based human resource management, knowledge-based identification and goal-setting and knowledge-based team building on knowledge-based universities, improving university performance, and improving individual performance is positive and significant. Findings can be used to improve knowledge management in universities.